Design And Fabrication of Multi- Fuel Biomass Cook Stove That Works on Both Rocket and Top-Lit Up Draft Gasification Principles (Journal of Science and Technology, 2025)
Heating water and food has been shown to be essential to human health, and heat is produced from different sources like electricity, gas, fossil fuel and biomass, for example. Electricity and gas are cleaner sources of energy used for cooking compared to traditional cooking methods that are used by lots of people in Sub-Saharan African countries, including Sierra Leone. Studies on traditional three stove fire have shown lower thermal efficiency and higher environmental pollution, while using scientific principles to design cookstoves lead to higher thermal efficiency and lower emissions. Consequently, this study was undertaken to address issues of pollution and  lower thermal efficiency by designing and producing an improved cook stove wherein scientific principles (Rocket and Top-lit up Draft), technical skills and locally available material were used. The produced stove was tested using procedures of the Water boiling tests. One of the results shows the highest temperature flame of 4880 C. Burning rate and specific fuel consumption were 2.47gram/sec and 0.56 Kgwood/Kgwater respectively. Additionally, fire power and thermal efficiency of 8.598kW and 41.37% respectively were also obtained. These results show that using scientific methods and skills to produce improved cookstoves will result in higher thermal efficiency and lower fuel consumption. These results do not only reflect positively on the environment, but on the health of women and children, considering their involvement in collection of wood used as fuel for cooking.